PEMBUATAN APLIKASI MONITORING DAN TRACKING BUS TRANS KOETARADJA BERBASIS ANDROID - Ayu Herlinda; ROmy Dharmawan (Ubudiyah Indonesia University, 2019)
One of the problems that's often faced in the big cities is the traffic jam caused by the growth of vehicles notaccompanied by the widening of the appropriate road and one of the alternatives to reduce congestion is by thepresence of Trans Koetaradja public bus. But the existence of Trans Koetaradja bus can not be detected by prospectivepassengers. Based on that situation trans koetaradja required an android-based system to monitor and mentracking thebus position so that prospective passengers doesn't have wait too long at the bus stop or missed the bus. This researchentitled